Peran Kader Surabaya Hebat dalam Pencegahan Penyakit Demam Berdarah Dengue di Kelurahan Klampis Ngasem - Sartika Devi Prameswari; Sri Windari; Gideon Setyo Budiwitjaksono; Mar’atus Sholikhatunnisa; Mohamad Zahrain Adjie; Moh Fatkhur Rohman; Jessica Putri Adiyoga; Melinda Trisya Yulianto; Syafira Puteri Maharani; Fiya Wardhatul Islamyi; Tia Ivanka (CV. ALIM'SPUBLISHING, 2024)
The JUMANTIK (Mosquito Larvae Monitoring Cadre) activity is an effort to prevent and control dengue fever through the inspection and monitoring of mosquito larvae in residential areas. This program is a collaboration between students of the Community Service Program (KKN) from UPNVJT and the Surabaya Hebat Cadres (KSH) of Klampis Ngasem RW01. The aim of this program is to raise awareness and community participation in maintaining environmental health and preventing the spread of dengue fever in Surabaya. Through this activity, it is expected that the community will become more active in maintaining environmental cleanliness and regularly monitoring the presence of mosquito larvae. The results of this program show an increase in public awareness and a decrease in the number of dengue fever cases in the monitored areas.